MEKANISME PERLINDUNGAN JUSTICE COLLABORATOR DALAM PENGUNGKAPAN KASUS PEMBUNUHAN BERENCANA - Citra Nabilla, Ayra; Kusumah, Haidan Angga (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
A Justice Collaborator is a perpetrator who works with law enforcement to help uncover a case by providing important information in a criminal act. A Justice Collaborator receives threats from various parties, therefore a Justice Collaborator needs to get adequate legal protection to ensure his safety and security. The protection of Justice Collaborators is regulated in Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. This study aims to analyze the protection mechanism given to justice collaborators in the disclosure of premeditated murder cases, both in terms of existing regulations and their implementation in the field. The results of the study show that even though there are regulations regulating the protection of justice collaborators, its implementation still encounters various obstacles. Some of the factors that affect the effectiveness of these protections include a lack of coordination between law enforcement agencies, limited resources, and threats to the safety of justice collaborators from parties involved in criminal acts. This study suggests improvements in the justice collaborator protection system through increased coordination between institutions, adequate resource allocation, and the application of strict sanctions for protection violations. Thus, the role of justice collaborators in the disclosure of premeditated murder cases can be more optimal and make a significant contribution to law enforcement in Indonesia.